DEVELOPMENT OF LEARNING VIDEO WITH OPEN ENDED APPROACH TO IMPROVE ABILITY MATHEMATICAL REASONING AND CRITICAL THINKING STUDENTS OF HIGH SCHOOL OF HIGH SCHOOL OF MUSLIMIN MEDAN IN MEDAN - Mia Yolanda Siregar; Hasratuddin Siregar; Hermawan Syahputra (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
This research was conducted in two stages, namely the first stage of developing learning videos with the Open Ended approach using the ADDIE development model, and the second stage testing the learning videos with the Open Ended approach which was developed in grades VIII-1 and VIII-2 SMP Ikhwanul Muslimin Medan. From the results of the first and second trials, it was obtained: 1) In the first and second trials there was an increase in the average value of students' mathematical reasoning abilities of 14.64; 2) In the first and second trials there was an increase in the average value of students' mathematical critical thinking skills of 7.29; 3) Learning videos with an Open Ended approach to improve mathematical reasoning and critical thinking skills have been effective to use;Keywords: development of learning videos, ADDIE model, Open Ended Approach, mathematical reasoning, mathematical critical thinking.